2014
DOI: 10.1007/s11010-014-2244-7
|View full text |Cite
|
Sign up to set email alerts
|

E2F1 regulates p53R2 gene expression in p53-deficient cells

Abstract: The p53R2 gene encoding a small subunit of the ribonucleotide reductase has been identified as a p53-inducible gene. Although this gene is discovered as a target for p53 family proteins, the mechanism underlying p53R2 induction by DNA damage in p53-defiencient cells remains to be elucidated. In this study, we demonstrate that transcription factor E2F1 regulates the p53R2 gene expression in p53-deficient cells. We found that p53R2 was a target for E2F1 in DNA damage response (DDR), because ectopic expression of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 31 publications
0
9
0
Order By: Relevance
“…30 It was shown that silencing p53R2 expression sensitizes CRC cancer cells to undergo apoptotic cell death in the presence of DNA damage agent. 46 These findings indicate that targeting p53R2 could enhance the effectiveness of ionizing radiation or DNA-damaging chemotherapy. Interestingly, in some tumors, p53R2 nuclear localization is much stronger than the cytoplasmic localization (Fig.…”
Section: Discussionmentioning
confidence: 95%
“…30 It was shown that silencing p53R2 expression sensitizes CRC cancer cells to undergo apoptotic cell death in the presence of DNA damage agent. 46 These findings indicate that targeting p53R2 could enhance the effectiveness of ionizing radiation or DNA-damaging chemotherapy. Interestingly, in some tumors, p53R2 nuclear localization is much stronger than the cytoplasmic localization (Fig.…”
Section: Discussionmentioning
confidence: 95%
“…Data for the RRM2B interaction network was downloaded from the BioGRID database [72] (10/25/2018) and analyzed by Cytoscape v. 3.6.1 [73]. Several interactions were added manually based on literature findings (RRM2B-FOXO3 [34], RRM2B-P21 [32], RRM2B-TP73 [74], RRM2B-E2F1 [33], RRM2B-MEK2 [75]).…”
Section: Interaction and Pathway Enrichment Analysismentioning
confidence: 99%
“…Since the expression of RRM2B, MYC and several other 8q-amplicon genes was increased, we next tested if the products of these genes within the 8q-amplicon interact with RRM2B. RRM2B is regulated by p53 and p21 [32] and transcriptional factors, such as, E2F1 [33]. E2F1 regulates RRM2B in the absence of p53, and FOXO3 [34].…”
Section: Rrm2b Protein Interaction Network Includes Co-amplified 8q-amentioning
confidence: 99%
“…However, as most of the currently used chemotherapeutic agents do have severe toxic effects, which may cause limitations in their usage, it would be worthwhile to consider having therapeutic agents that simultaneously have improved efficacy and less toxicity. Doxorubicin [DOX, C27H29NO11, (7S,9S)‐7‐[(2R,4S,5S,6S)‐4‐amino‐5‐hydroxy‐6‐methyloxan‐2‐yl]oxy‐6,9,11‐trihydroxy‐9‐(2‐hydroxyacetyl)‐4‐methoxy‐8,10‐dihydro‐7H‐tetracene‐5,12‐dione], an anthracycline, has been recognized as one of the main chemotherapeutic agents, which is used for various cancer therapy including: colon, breast, lung cancers and also for acute leukaemia and lymphomas . DOX works by inhibiting the enzyme topoisomerase II that in turn results in stopping of DNA replication processes.…”
Section: Introductionmentioning
confidence: 99%
“…Doxorubicin [DOX, C27H29NO11, (7S,9S)-7-[(2R,4S,5S,6S)-4-amino-5-hydroxy-6-methyloxan-2-yl]oxy-6,9,11-trihydroxy-9-(2-hydroxyacetyl)-4-methoxy-8,10-dihydro-7H-tetracene-5,12-dione], an anthracycline, has been recognized as one of the main chemotherapeutic agents, which is used for various cancer therapy including: colon, breast, lung cancers and also for acute leukaemia and lymphomas. [3] DOX works by inhibiting the enzyme topoisomerase II that in turn results in stopping of DNA replication processes. Generation of free radicals that induces DNA and cell membrane damages is another mechanism of action for DOX chemotherapeutic effects.…”
Section: Introductionmentioning
confidence: 99%